Proceso de atención de enfermería a paciente de 27 años de edad con osteomielitis. - Parra Sánchez, Martha María (2020)
Osteomyelitis is an infection of the bone usually caused by bacteria. when a bone is infected, the bone marrow usually becomes inflamed, causing pressure and preventing the circulation of blood to the bone. the infection can spread outside the bone forming an abscess in the soft tissues. the clinical case presented correspond to a 27-year-old patient with chronic osteomyelitis after suffering a traffic accident that caused a fracture at the level of the tibia and the right fibula, more or less than 5 centimeters with exposure of the bone. unable to walk there is presence of purulent whitish discharge and bleeding. on september 25th, 2019 he was admitted receiving antibiotic treatment, therapies, and laboratory tests. x-ray was performed on the patient, which reflected the presence of elastic titanium nails at the level of the tibia and fibula, the presence of infected pseudoarthrosis, the patient was maintained with wound cleaning for subsequent surgical intervention. the patient was taken to the operating room for cleaning and extraction of material, a devitalized tissue was found which was also removed, bone curettage was performed, and it was covered with gauze soaked in antibiotic. then he was taken to the post-operative room. he is maintained with antibiotic-therapy plus surgical cleaning. on october 19th, 2019, the patient with osteomyelitis was healing, he was afebrile, painless, in good general condition, normal biological functions, normal vital signs, good prognosis for life with hospital discharge.